A new class of quaternary ammonium compounds as potent and environmental friendly disinfectants. (15th December 2022) - Wang, Guodong; Yang, Ling; Jiang, Libin; Chen, Jingyi; Jing, Qian; Mai, Yuhan; Deng, Lina; Lin, Yuxin; Chen, Liyun; Chen, Zheng; Xu, Peng; Jiang, Longguang; et al.
Abstract: Quaternary ammonium compounds (QACs) are inexpensive and readily available disinfectants, and have been widely used, especially since the COVID-19 outbreak. The toxicity of QACs to humans has raised increasing concerns in recent years. Here, a new type of QACs was synthesized by replacing the alkyl chain with zinc phthalocyanine (ZnPc), which consists of a large aromatic ring and is hydrophobic in nature, similar to the alkyl chain of QACs. Three ZnPc-containing disinfectants were synthesized and fully characterized. These compounds showed 15–16 fold higher antimicrobial effect against Gram-negative bacteria than the well-known QACs with half-maximal inhibitory (IC50 ) values of 1.43 μM, 2.70 μM, and 1.31 μM, respectively. With the assistance of 680 nm light, compounds 4 and 6 had much higher bactericidal toxicities at nanomolar concentrations. Compound 6 had a bactericidal efficacy of close to 6 logs (99.9999% kill rate) at 1 μM to Gram-positive bacteria, including MRSA, under light illumination. Besides, these compounds were safe for mammalian cells. In a mouse model, compound 6 was effective in healing wound infection. Importantly, compound 6 was easily degraded at working concentrations under sunlight illumination, and is environmentally friendly. Thus, compound 6 is a novel and promising disinfectant. Graphical abstract: Image 1 Highlights: Quaternary ammonium compounds (QACs) degrade slowly in environment, causing health concerns. A new type of QACs containing phthalocyanine group are synthesized. New QACs degrade fast under environmental lighting. New QACs show 15–16 times stronger bactericidal effect. New QACs kill 6 logs of Gram-positive bacteria at 1 μM.